HAKEKAT DAN TUJUAN HIDUP MANUSIA DAN HUBUNGANNYA DENGAN TUJUAN PENDIDIKAN ISLAM - Trinurmi, Sitti (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2015)
Islamic education is the task of guiding and directing the development and learners from stage to stage up to the point of optimal. The purpose of education is to create a good man (al-insan al-Salih) that is certain is universal and it is definitely recognized everyone and everything flows without questioning in any country and any religion. Lots of really what was raised by the experts Muslims but are all essentially the same as above. Besides that education is also to enhance human morals. Basic philosophy and goals of Islamic education is essentially identical to the basis and purpose of Islam or rather the goal of Islam itself. The nature and purpose of human life is the nature and purpose of human life associated with the nature and objectives of Islamic education is to educate individuals virtuous with regard to the development of spiritual, emotional, social, intellectual and physical, educate members of social groups devout, both in the family and the Muslim community.